2023
DOI: 10.3233/wor-205075
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the correlation between hand grip strength and muscle mass, balance, mobility, and daily life activities in elderly individuals living in nursing homes

Abstract: BACKGROUND: Aging is a process that includes progressive physiological changes. Grip strength is an important indicator of current health in the elderly. OBJECTIVE: The aim of the study was to examine the correlation between dominant-hand grip strength (HGS) and cognitive function, mid-upper arm circumference, muscle-bone mass, balance, mobility, and daily life activities in elderly individuals living in nursing homes and determine the effect rates of these factors on HGS. METHODS: Seventy-two elderly individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Given that aging is a complex process, many factors contribute to a general decline in motor functions. They include the physiological reduction in muscle mass (Soyuer et al, 2023), reduced coordination or neuromuscular impairments (Carson, 2018; Clark, 2019), as well as changes in sensory, visual, and attention capabilities (Heintz Walters et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Given that aging is a complex process, many factors contribute to a general decline in motor functions. They include the physiological reduction in muscle mass (Soyuer et al, 2023), reduced coordination or neuromuscular impairments (Carson, 2018; Clark, 2019), as well as changes in sensory, visual, and attention capabilities (Heintz Walters et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Given that aging is a complex process, many factors contribute to a general decline in motor functions. They include the physiological reduction in muscle mass ( Soyuer et al, 2023 ), reduced coordination or neuromuscular impairments ( Carson, 2018 ; Clark, 2019 ), as well as changes in sensory, visual, and attention capabilities ( Heintz Walters et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review investigating the association between PA and grip strength confirmed the relationship between total PA, moderate-to-vigorous PA, light PA, and grip strength 41 . Furthermore, several reports have shown a relationship between grip strength and ADL independence in older individuals requiring nursing care 42,43 . Therefore, grip strength, which is related to maintaining independence in daily life and activity levels, may suppress the decline in cognitive function.…”
Section: Discussionmentioning
confidence: 99%